EFFECT OF CLIMATE CHANGE-INDUCED MIGRATION ON FOOD SECURITY OF FARMING HOUSEHOLDS IN SELECTED LOCAL GOVERNMENT AREAS OF ABIA STATE, NIGERIA - ONYA , S. C.; EJIBA, I. V. (The Faculty of Agriculture Obafemi Awolowo University, Ile-Ife, Nigeria., 2020)
The study examined the effect of climate change-induced migration on food security status of farming households using 120 households selected from four communities in Abia State, Nigeria. Data were analyzed using descriptive statistics, FGT and probit model. The result showed that climate change-induced migrants more likely come from households with older heads that are less educated as compared with non-migrant household heads. There was high perception of climate change incidences (flooding and erosion 93.33%, irregular and unpredictable rainfall patterns 85%, increased incidence of pest and disease 81.67%) by the farming households in the area. In spite of this, a high percentage of the households (43%) do nothing in the form of adaptation. The food security of households based on their migration status showed that 47% and 31% of migrant and non-migrant households were food secure respectively. The mean monthly food expenditure of migrant households was N49535.13 while non-migrant households was N40493.12 with p-value of 2.24 which showed that migration significantly influenced food security in the study area.  The probit regression result showed that climate change-induced migration significantly improved food security status of farming households. Also, education, access to credit, farm size and remittance significantly influenced the food security of the farming households in the study area. The study therefore, recommends the need for the government to provide the necessary incentives for people living in climate ravaged communities to encourage them relocate from high risk areas to low risk areas.